Violencias relatadas, derechos debatidos y mujeres movilizadas: el aborto en la agenda política de las mujeres indígenas en Argentina - Silvana Sciortino (Caravelle)
In this paper, I will assess the debates put forward by indigenous women on the struggles for the legalization or decriminalization of abortion in Argentina. More specifically, I will study the meanings related to the concepts of culture and identity. I aim to analyze the ways in which the various meanings associated with these concepts, as categories of political assertion, weave together into several standing points on indigenous women’s rights as women, and on priority markings within their political agenda.